Rotational atherectomy: assessment of the effectiveness and safety. (3rd October 2022) - Borges-Rosa, J; Grine, M; Oliveira-Santos, M; Delgado-Silva, J; Matos, V; Costa, M; Goncalves, L
Abstract: Background: Rotational atherectomy (RA) enables percutaneous coronary intervention (PCI) for complex and calcified coronary lesions, despite limited data regarding long-term outcomes. Purpose: We aimed to characterize success rate, safety, and long-term outcomes with this technique in a single-centre with over a decade of experience. Methods: We retrospectively analysed all cases of RA performed in a single-centre between January 2009 and December 2020. Angiographic success was defined as the presence of less than 30% residual stenosis and grade 3 TIMI (thrombolysis in myocardial infarction) flow. Complications included coronary perforation or dissection, burr entrapment, wire fracture, slow flow/no-reflow, side branch occlusion, peri-procedural myocardial infarction (MI), or death. Long-term major adverse cardiovascular (CV) events (MACE) included CV and all-cause death, MI, and target vessel revascularization. Results: Of the total of 14, 527 PCI performed, 410 procedures (2.8%) included RA. Most patients were male (74.0%) with mean age of 72.3±9.3 years. There was high prevalence of hypertension (85.65%) and dyslipidaemia (74.2%) which increased significantly over time (p trend=0.008 and p trend<0.001, respectively). One-third presented with acute coronary syndrome, most patients had multivessel disease (38.4% two-vessel, 32.7% three-vessel), and 12.2% had significant left main disease. Over time there was an increase in disease complexity, reflected by the proportion of type B2/C lesions (p trend =0.003) and median SYNTAX score (p trend =0.003). The utilization of transradial access increased over time (p trend =0.003) and maximum burr size was ≤1.50 mm in most cases (88.0%), with smaller sizes over time. Overall angiographic success rate was 96.6% without significant variation over time while complications (9.0%) showed a temporal decline (p trend=0.029) (Figure 1). Most frequent complications were coronary dissection (n=17) and burr entrapment (n=6). After a median follow-up of 40 (16–76) months, MACE occurred in 27.7% of patients, mainly due to CV death. At one year of follow-up, MACE, all-cause mortality and target vessel revascularization occurred in 12.1%, 6.4%, and 5.6%, respectively, without variation over time. Conclusions: RA is an effective and safe technique, with a declining rate of peri-procedural complications along with technical developments. The rate of long-term events is concordant with the CV risk profile and coronary lesion complexity. Funding Acknowledgement: Type of funding sources: None.